Predicting academic achievement in English medium instruction in Vietnam: a multidimensional approach using standardised testing and vocabulary assessment - Cao, Hong Phat (2025)
English-medium instruction (EMI) programmes are increasingly central to higher education (HE) worldwide, fostering internationalisation, academic collaboration, and global workforce readiness (Lasagabaster, 2022; Macaro et al., 2018). Vietnam, striving to align with this trend, faces challenges, such as the absence of consistent and standardised guidelines for using English language proficiency (ELP) assessments for admission purposes (e.g., Dang & Moskovsky, 2023; Nguyen et al., 2017; Tran & Nguyen, 2018). This thesis addresses these challenges by focusing on the role of ELP assessments–specifically the Pearson Test of English Academic (PTEA)–as tools for evaluating students’ academic readiness in EMI settings. Although widely adopted in recent years (Pearson-PTE, n.d.), the PTEA’s construct validity remains underexplored (Durrant et al., 2015; Riazi, 2013). This raises questions about its effectiveness, as meta-analyses consistently highlight the limited predictive power of standardised ELP tests (e.g., Abunawas, 2014; Gagen & Faez, 2024; Ihlenfeld & Rios, 2023). Through three interconnected studies–a systematic review of the PTEA’s construct validity, an empirical investigation into its predictive validity, and an analysis of lexical complexity in academic writing–this thesis highlights the significance of understanding the constructs measured by the PTEA alongside predictors of academic achievement within EMI programmes.